Suitability of Current Single-Cylinder Diesel Engines Available in Indonesia with New Indonesian National Standard (SNI 119:2020) - Kurnia Fajar Adhi Sukra; Hari Setiapraja; Respatya Teguh Soewono; Hari Sumartono (ASEAN Journal on Science and Technology for Development, 2022)
Diesel engines have been utilized for various purposes in Indonesia. Diesel engine manufacturers have developed designs and competed with each other to win the market in Indonesia. Nationally and internationally recognized standards are required to ensure the quality of products for Indonesia and the international market. The Indonesian National Standard (SNI) 119 is one of the recognized standards for single-cylinder diesel engine in Indonesia. Compared with the previous SNI 0119:2012, SNI 119:2020 has revised the limits of some parameters. This study evaluated the passing data of SNI test results from 2015 to 2020 and then analyzed the distribution of engines in each class for the comparison of limits between SNI 0119:2012 and SNI 119:2020 using normal distribution. Results showed that class D engines have the highest probability of passing the new limit of SNI 119:2020 at 98.59% to 100%. Meanwhile, class B has the lowest probability of acceptance at 38.68%. Power is the test parameter with the highest level of suitability, and specific fuel consumption is the parameter with the highest level of discrepancy for changes in SNI 119:2020.